Quantification of proteinuria by urine protein creatinine ratio in a single void urine in pre-eclamptic women and its correlation with 24 hours urinary protein - Saxena, Rashmi; Sharma, Manisha; Ranjan, Rajeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Proteinuria is a major indicator of hypertensive disorders of pregnancy. Though 24 hr urinary protein is considered to be the gold standard for evaluation of proteinuria in preeclampsia but its collection is time consuming, cumbersome and needs admission of the patient. The role of spot UPCR in random sample proposed as an alternative Method: A observational cross-sectional study was conducted from 2020 to 2021 on 78 antenatal women of gestational age >20 weeks meeting the inclusion and exclusion criteria were enrolled into this study. Data was compared by using Pearson correlation coefficient (r). ROC curve was plotted for spot UPCR value for detecting significant proteinuria (>300 mg/24 hr). Result: The quantification of proteinuria by spot UPCR strongly correlated with 24hr urinary protein. The p=0.001. There was a positive correlation of 24hr urine protein (mg/24 hr) with spot UPCR urine sample which was significant statistically (r=0.997, p<0.05) ROC curve analysis of Spot UPCR for proteinuria (>300 mg/24 hr) after the 20 weeks gestation. The spot UPCR showed significant large area under the curve (AUC) on the ROC curve. There is positive correlation between 24 hr urinary protein (>300 mg/24 hr) and spot UPCR in patients of pre-eclampsia Conclusions: From our study we concluded that spot urinary protein creatinine ratio has a significant linear correlation with 24 hr urinary protein in pre-eclampsia.